A Probe into the Intervention Mechanism of Yiqi Huayu Jiedu Decoction on TLR4/NLRP3 Signal Pathway in Lipopolysaccharide-Induced Acute Respiratory Distress Syndrome (ARDS) Rats. (18th February 2022) - Ma, Yuanhong; Chen, Yifan; Li, Yan; Liu, Yan; Kong, Yurong; Zou, Qiao; Guo, Zhengguang; Li, Xin; Chu, Yan; Wang, Qian
Abstract : Background . This study discusses the anti-inflammatory mechanism of Yiqi Huayu Jiedu decoction (YQHYJD) and studies the intervening effect of YQHYJD on the inflammatory cytokines in acute respiratory distress syndrome (ARDS) rats by inhibiting the TLR4/NLRP3 signal pathway. The aim of the probe is to provide evidence to support the identification of therapeutic targets in Chinese medicine treatment, which broadens the alternatives for the treatment of ARDS. Method . A lipopolysaccharide (LPS)-induced ARDS model group is established on rats by tail vein injection. A medicine group is established on ARDS rats by prophylactic administration using YQHYJD. Materials are collected, and tests are conducted according to experimental processes. Result . The rats in the medicine group gained weight compared with those in the ARDS model group. Pathological sections from the medicine group indicated improved condition in terms of pulmonary and interstitial edema in the lung tissues of rats compared with that from the ARDS model group. The percentage of neutrophil of the medicine group was significantly brought down compared with that of the ARDS model group (P < 0.001 ). Enzyme-linked immunosorbent assay (ELISA) was used to detect the changes in the level of inflammatory cytokines. It was observed that the levels of IL-1 β and IL-18 in serum of the medicine group significantly decreased (P < 0.001 and P < 0.01 ), the contents of TLR4 and NLRP3 in bronchoalveolar lavage fluid (BALF) of the medicine group decreased, and the contents of TLR4 and NLRP3 in lung tissue homogenate of the medicine group significantly decreased (P < 0.05, P < 0.001, P < 0.01, and P < 0.05 ). In further mass spectrum identification of the proteins from the same animal groups, it was observed that the expressions of inflammatory proteins TNFRSF1, LBP, and NOS2 of the medicine group were reduced. The differences were statistically significant. Conclusions . The pharmacological action of YQHYJD's anti-inflammatory mechanism is closely associated with the regulation of inflammatory cytokines TLR4, NLRP3, IL-1 β, IL-18, TNFRSF1, LBP, and NOS2 on the TLR4/NLRP3 signal pathway.